Manipulasi Agronomi Bunga Iles-iles (Amorphophallus muelleri Blume) untuk Meningkatkan Produksi Biji - Edi Santosa; Ani Kurniawati; Maryati Sari; Adolf Pieter Lontoh (Institut Pertanian Bogor, 2016)
Corm of iles-iles (Amorphophallus muelleri Blume) is extracted for glucomannan production, a material that is widely used in medicinal, food, and beverage industries. Increasing demand on glucomannan promotes fast expansion of planting area in Indonesia, however, seed availability is limited. The objective of the experiment was to study corm age, planting distance, and planting depth in order to enhance seed production in A. muelleri. Two experiments were conducted under paranet of 65% in Leuwikopo Experimental Farm, Bogor Agricultural University (IPB) from June-November 2015. First experiment used 0- (bulbils), 1-, 2-, 3-, and 4-year-old corms. Second experiment used flowering 3-year-old corms, arranged by factorial of planting distance (0 × 0 cm and 50 × 50 cm) and planting depth (0 and 5 cm in depth). Results showed that flowering of A. muelleri was dependent on corm age, 96% of 3-year-old corms produced flower but none of the 1- and 4-years-old corms produced flower, whereas 8% of 2-year-old corms produced flower. Planting distance did not affect flower growth, while planting at a depth of 5 cm enhanced seed production. Present experiments imply that application of large 3-year-old corms, planting in dense population and at depth of 5 cm could enhance seed production of A. muelleri. It needs further investigation on seed quality from flowering of present treatments.